Variation und Wandel. Zur Konkurrenz morphologischer und syntaktischer A+N-Verbindungen im Deutschen und Niederländischen seit 1700 - Schuster, Saskia (Konvergenz und Divergenz. Sprachvergleichende Studien zum Deutschen, 2016)
The volume covers the development of concurrence in morphological and syntactic A+N naming units such as Gelbfieber (yellow fever) and schwarzer Markt (black market) in German and Dutch since 1700. Using historical case studies, it examines the development of such combinations in view of the principles of construction grammar. In addition, the study also explores potential factors that have fostered divergence between the two languages.